A systematic literature review on Shari’ah governance mechanism and firm performance in Islamic banking - Haron, Razali; Nomran, Naji (Emerald Publishing Limited, 2020)
Abstract Purpose – This paper aims to systematically review the existing studies on the relationship of Shari’ah governance (SG), as represented by the Shari’ah supervisory board (SSB), with firm performance of Islamic banks (IBs), to suggest opportunities for future research in this field. Design/methodology/approach – By adopting a systematic literature review, 21 empirical and theoretical papers published in Scopus concerning the relationship between SSB and performance of IBs were selected for review and analysis. Findings – In light of the existing research studies’ limitations, this paper suggests that the effect of SSB on IBs’ performance still requires more empirical analyses using alternative analytical methods, alternative measures, and different periods (during crisis and non-crisis). Besides that, these studies should take into account the differences across jurisdictions in their SG models, the degree of agencies’ intervention in SG practices, the control over cross-memberships of scholars, and the differences across IBs in the position of SSB in the organization structure. Practical implications – The analysis undertaken in this paper would address the literature gaps on the effect of SSB on IBs’ performance as this study serves as a guide for the researchers, academicians, and interested researchers from Islamic international autonomous non-for-profit organizations, e.g. AAOIFI and IFSB in research related to this important area. Importantly, the findings of this study would support regulators and related authorities across jurisdictions with suggestions on improving the current SG practices. Originality/value – This paper presents a critical review of the existing research on SSB and IB performance and suggests new variables, measurements, analytical methods, and new issues for researchers in this area. Thus, it identifies the literature gap that still needs further empirical investigation and a suitable way to close it. Keywords Shari’ah governance, Shari’ah supervisory board, Performance, Islamic banks, Systematic literature review Paper type Literature review